2003
DOI: 10.1136/bmj.327.7409.260
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective review of care and outcomes in young adults with type 1 diabetes

Abstract: smoke but, as there are no data directly relating cotinine levels to risk of death, it is not possible to predict the likely effect of a reduction of this magnitude on the risk of sudden infant death. Our results also suggest that harm reduction measures short of a total ban on smoking in the home are likely to have little effect on the exposure of infants to tobacco smoke, but this requires verification with a larger sample.We thank the parents who participated; the health visitors, their managers, and staff … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
3
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 4 publications
6
70
3
1
Order By: Relevance
“…In our cohort, the poorer glycemic control was largely confined to adolescent patients. While adolescents, in general, tend to experience worse glycemic control than younger children [12], immigrant youth may face additional challenges as they struggle with the normal adolescent task of fitting in with their peers. Socioeconomic factors may also play a role in poor diabetes control in Somali adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, the poorer glycemic control was largely confined to adolescent patients. While adolescents, in general, tend to experience worse glycemic control than younger children [12], immigrant youth may face additional challenges as they struggle with the normal adolescent task of fitting in with their peers. Socioeconomic factors may also play a role in poor diabetes control in Somali adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…2 The mean HbA 1C of 8.4% achieved in our study is the same as that in DAFNE trial 12 and in the conventional therapy cohort in DCCT 2 and better than that reported (9.4%) in the multicentre study. 4 Important factors were better clinic attendance, more frequent and more structured visits, regular HbA 1C levels, and close collaboration involving the entire diabetes care team and users.…”
Section: Discussionmentioning
confidence: 99%
“…No Australian data are available on rates of successful transition from paediatric to adult care and association with diabetes outcomes in young adults. Such data would seem important to gather in view of data suggesting poor clinical and psychiatric outcomes in young adults with type 1 diabetes 68,81 , 82 . Also, standardised Australian mortality data are also not available for children and adolescents with diabetes.…”
Section: Discussionmentioning
confidence: 99%